Особливості маркетингової діяльності в соціальних мережах - Романишин, С. Б.; Греськів, І. Р. (Видавництво Львівської політехніки, 2015)
Розглянуто особливості використання, значення й тенденції розвитку маркетингу в соціальних мережах, що сьогодні стає дедалі популярнішим завдяки оперативності, невисокій ціні, цільовому характеру, високому ступеню довіри тощо. Подано результати опитування маркетологів розвинених країн щодо використання ними такого маркетингу. Представлено модель використання соціальних мереж у маркетинговій діяльності, виділено види бізнесу й галузі діяльності, в яких вони найпоширеніші. Розкрито ключові методи та підходи до маркетингу в соціальних мережах. In the article features of the usage, importance and trends of marketing in social networks, which is becoming more popular because of its speed, low price, target character, a high degree of trust, are described. The results of a survey of marketers from developed countries concerning the use of such marketing are presented. The model of social networking in marketing activities is given and types of business and industries in which marketing in social networks is the most widespread are described. The key methods and approaches to marketing in social networks are revealed. Over 80 % of Ukrainian Internet users use social networks, and it is difficult to imagine life without them. Thus marketing is getting reoriented now on social media. Marketing in social networks - is certainly interesting and trendy marketing. However, despite the extensive experience in promoting brands in social media, not all companies know how to do it and do not use the full range of tools which can and should work in social networks. Social networking is one of the most popular types of entertainment, so it is not surprising that advertising on social networks in the US and Western Europe has become very popular. Today, advertising and promotion in social networks are the most important and successful means of SMM in internet marketing. According to the “2015 Social Media Marketing Industry Report” 96 % among respondents -marketing experts from around the world – are engaged in social marketing and 92 % said that it is extremely important for their business. Marketing in social networks, like any other form of advertising has its advantages and disadvantages, positive and negative effects that can affect not only the advertised product, but the whole enterprise. On one hand, using social networking allows to attract a significant number of customers, increase profit. On the other hand - social networking is a possibility to quickly share experiences, so if only one user discovers that advertised goods or services have serious shortcomings, it will be soon found out by a large amount of people. In this case, product promotion can trigger counterproductive effects. Therefore, when deciding on engaging social networks to implement marketing strategy, marketers should thoroughly approach this issue and make a detailed analysis of the situation which has arisen or may arise during an activity. The effects of the implementation of such marketing activities will depend on several factors: the scope of the company, product or service and its features, target audience and others.
Peculiarities of marketing in social networks
Keywords: маркетинг; маркетингова діяльність; соціальні мережі; маркетинг у соцмережах; marketing; marketing activity; social network; marketing in social networks